Nicolau Maquiavel: o estudo do Príncipe e a preservação da ordem como forma de governo - Nascimento, José Pablo Rodrigues Francisco do (2023)
The present research aims to highlight the political ideas expressed by Nicolau Machiavelli in his work "The Prince", establishing connections between the characteristics of government and Italian society in the 16th century, with the purpose of ensuring political unity. The preparation of this document will be divided into three distinct parts: a historical foundation that relates to Italy in Machiavelli's time; a study to highlight the importance of defending the State and the relationship between the people and the sovereign; and, finally, an objective conclusion that will present the ruler's responsibilities and their relationship with the challenges that involve the construction of a political unit. We will use the ideas proposed by Machiavelli to explain the political maintenance of the Modern State, addressing the challenges linked to public administration and seeking solutions to the problems that affect Italian cities. At the end, we will dedicate a section of the study to political thought and its interaction with modern political theory, highlighting the importance of Machiavelli's approach to sovereignty and political unity. We will consider not only the philosophical aspect of these questions, but also a critical approach, giving the text a positive perspective that, although not exclusive to Machiavelli, certainly prevails in modern political theory.